1997
DOI: 10.1177/096973309700400107
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Ethics: Effect on Moral Development

Abstract: The purpose of this study was to determine the development of moral judgement in first-year and senior baccalaureate nursing students. These students were enrolled in three separate nursing programmes, each of which differed significantly in ethical content. The sample totalled 180 students enrolled in three New England programmes. Programme A included an ethics course taught by a professor of ethics. Programme B integrated ethical issues into all nursing theory courses. Programme C did not include ethical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 7 publications
1
12
0
1
Order By: Relevance
“…In this period, age, maturity and education can play important roles. Many studies on general moral development in young adults indicate that increases in cognitive ability, maturity and educational experiences lead to a general increase in moral reasoning skills . However, the findings of the present study provide evidence to contest these perspectives on the trajectory and growth of moral reasoning.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this period, age, maturity and education can play important roles. Many studies on general moral development in young adults indicate that increases in cognitive ability, maturity and educational experiences lead to a general increase in moral reasoning skills . However, the findings of the present study provide evidence to contest these perspectives on the trajectory and growth of moral reasoning.…”
Section: Discussionsupporting
confidence: 90%
“…The period of transition from conventional to post‐conventional morality is critical and, usually, occurs in late adolescence and young adulthood . During this period, education can play an important role and many studies have confirmed the positive effects of education on moral development . However, there is evidence that this may not be the case in medical education.…”
Section: Introductionmentioning
confidence: 99%
“…(1995) found a significant improvement in moral reasoning (based on the DIT) of medical students following the completion of a 3‐month course on the philosophy of medicine that included teaching of medical ethics. Krawczyk (1997) studied nursing students in three different programmes. One programme included an ethics course with group participation and a decision‐making component, while the other two programmes did not.…”
Section: Discussionmentioning
confidence: 99%
“…In two cross‐sectional studies, one in Finland reported a significantly higher P score in senior level students compared to first year students (Auvinen et al . 2004), and the other in the USA found senior students scored higher than junior students at three different college nursing programmes (Krawczyk 1997). Three longitudinal studies have been published.…”
Section: Introduction and Purposementioning
confidence: 99%
“…Various sources provide support for the value of discussion experiences in bioethics (Cassels & Redman 1989, Lovett & Seedhouse 1990, Derse & Krogull 1994, Davis 1997, Krawczyk 1997, Strong et al . 1997, Makoul & Curry 1998, Self et al .…”
Section: Introductionmentioning
confidence: 99%